Implicit Differentiation

This very powerful differentiation process follows from the chain rule.
$$u = g(f(x)) \
\frac{du}{dx} = g'(f(x)) \times f'(x)$$
We’ve done quite a few differentiation and derivatives, but they all have been differentiation of functions of the form \( y = f(x) \). Not all the functions will fall into this simple form. The process that we are going to cover is called implicit differentiation.
The following examples require the use of implicit differentiation. The essential skill of implicit differentiation is exactly a special case of the chain rule for derivatives. Let’s take a look at them now!

Question 1

Find \( \dfrac{dy}{dx} \) for \( xy = 1 \).

\( \begin{aligned} \displaystyle \require{color}
\frac{d}{dx}xy &= \frac{d}{dx}1 \\
\frac{d}{dx}x \times y + x \times \frac{d}{dx}y &= 0 &\color{red} \text{product rule}\\
1 \times y + x\frac{dy}{dx} &= 0 \\
y + x\frac{dy}{dx} &= 0 \\
x\frac{dy}{dx} &= -y \\
\therefore \frac{dy}{dx} &= -\frac{y}{x} \\
\end{aligned} \\ \)

Question 2

Find \( \dfrac{dy}{dx} \) for \( x^2 + y^2 = 1 \).

\( \begin{aligned} \displaystyle \require{color}
\frac{d}{dx}x^2 + \frac{d}{dx}y^2 &= \frac{d}{dx}1 \\
2x + 2y \times \frac{dy}{dx} &= 0 &\color{red} \text{chain rule}\\
2y \times \frac{dy}{dx} &= -2x \\
\frac{dy}{dx} &= -\frac{2x}{2y} \\
\therefore \frac{dy}{dx} &= -\frac{x}{y} \\
\end{aligned} \\ \)

Question 3

Find \( \dfrac{dy}{dx} \) for \( x^4y^5 = y + 1 \).

\( \begin{aligned} \displaystyle
\frac{d}{dx}x^4 \times y^5 + x^4 \times \frac{d}{dx} y^5 &= \frac{d}{dx}y + \frac{d}{dx}1 \\
4x^3y^5 + x^4 \times 5y\frac{dy}{dx} &= \frac{dy}{dx} + 0 \\
4x^3y^5 + 5x^4y\frac{dy}{dx} &= \frac{dy}{dx} \\
5x^4y\frac{dy}{dx} – \frac{dy}{dx} &= -4x^3y^5 \\
(5x^4y -1)\frac{dy}{dx} &= -4x^3y^5 \\
\therefore \frac{dy}{dx} &= -\frac{4x^3y^5}{5x^4y -1} \\
\end{aligned} \\ \)

Question 4

Find \( \dfrac{dy}{dx} \) for \( \sin{y} = x \).

\( \begin{aligned} \displaystyle
\frac{d}{dx} \sin{y} &= \frac{d}{dx}x \\
\cos{y} \times \frac{dy}{dx} &= 1 \\
\therefore \frac{dy}{dx} &= \frac{1}{\cos{y}} \\
\end{aligned} \\ \)

Question 5

Differentiate \( \cos{xy} \) in terms of \( x \).

\( \begin{aligned} \displaystyle
\frac{d}{dx} \cos{xy} &= – \sin{xy} \times \frac{d}{dx}xy \\
&= -\sin{xy} \times \Big(\frac{d}{dx}x \times y + x \times \frac{d}{dx}y\Big) \\
&= -\sin{xy} \times \Big(y + x\frac{dy}{dx}\Big) \\
\end{aligned} \\ \)

Question 6

Find \( \dfrac{dy}{dx} \) for \( \cos^2{x} + \cos^2{y} = \cos{(x+y)} \).

\( \begin{aligned} \displaystyle \require{color}
\frac{d}{dx}\cos^2{x} + \frac{d}{dx}\cos^2{y} &= \frac{d}{dx}\cos{(x+y)} \\
2 \cos{x} \times \frac{d}{dx} \cos{x} + 2 \cos{y} \times \frac{d}{dx}\cos{y} &= -\sin{(x+y)} \times \frac{d}{dx}(x+y)\\
2 \cos{x} \times (-\sin{x}) + 2 \cos{y} \times (- \sin{y}) \times \frac{dy}{dx} &= – \sin{(x+y)} \times \Big(1+\frac{dy}{dx}\Big) \\
-2 \sin{x} \cos{x} – 2 \sin{y} \cos{y} \frac{dy}{dx} &= – \sin{(x+y)} – \sin{(x+y)} \frac{dy}{dx} \\
\sin{(x+y)} \frac{dy}{dx} – 2 \sin{y} \cos{y} \frac{dy}{dx} &= 2 \sin{x} \cos{x} – \sin{(x+y)} \\
(\sin{(x+y)} – 2 \sin{y} \cos{y}) \frac{dy}{dx} &= 2 \sin{x} \cos{x} – \sin{(x+y)} \\
\therefore \frac{dy}{dx} &= \frac{2 \sin{x} \cos{x} – \sin{(x+y)}}{\sin{(x+y)} – 2 \sin{y} \cos{y}} \\
\end{aligned} \)

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Chain Rule Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume

 



Your email address will not be published.